Segment Routed Traffic Engineering with Bounded Stretch in Software-Defined Networks - Settawatcharawanit, Tossaphol; Suppakitpaisarn, Vorapong; Yamada, Shigeki; Ji, Yusheng (2018 IEEE 43rd Conference on Local Computer Networks (LCN), 2018)
Segment Routed Traffic Engineering is emerging as an important application for network operators to manage resource utilization by using segment routing paths as candidates for route selection. In order to facilitate the network operator demands, a traffic engineering program should be fast and efficient. These two characteristics are very essential since the traffic engineering program must be invoked periodically in short intervals. The segment routing paths can be constructed by concatenating the shortest paths between two nodes such that there is a path from source to destination. We are interested in the problem to find intermediate nodes to construct segment routing paths minimizing the maximum link utilization. However, the existing approaches have the shortcomings that either they require a substantial amount of time to find a solution or they must sacrifice a considerable amount of link utilization. To address these issues, we propose to limit the number of intermediate node candidates by using a bounded stretch constraint relative to the shortest path of the source-destination pair. Then, we evaluate the computation time and link utilization against the existing work. We show that the bounded stretch constraint helps reduce the computation time while a near optimal link utilization can be achieved.